Employee Reward as Moderator in The Relationship Between Transformational Leadership Style on Employee Motivation in Construction Organisations in UAE - ABULAWI, RAKAN HAKEM HASAN (2022)
This study aims to investigate the moderating effects of extrinsic and intrinsic employee rewards on the relationship between transformational leadership style and employee motivation in construction organisations in the UAE. The data were collected through a questionnaire distributed among the employees of different construction organisations in UAE to investigate their opinions. The data collected from 144 employees were analysed using a combination of inferential and descriptive statistics. All of the statistical analyses were performed using IBM's SPSS 28 statistical package. The study findings revealed a significant positive relationship between intrinsic and extrinsic employee rewards and employee motivation for construction sector workers in UAE. Also, the study’s results suggest that there is not enough evidence supporting the notion that the presence or absence of intrinsic and extrinsic rewards affect the impact of transformational leadership style on employee motivation for construction employees in UAE. The study's findings were compared with those of previous research. The study's limitations and the theoretical and practical implications of the findings were acknowledged. Moreover, the study's findings are expected to help develop a comprehensive understanding of the relationship between employee rewards, transformational leadership style and the motivation of construction employees in UAE.